2020
DOI: 10.1158/0008-5472.can-19-2039
|View full text |Cite
|
Sign up to set email alerts
|

Linking Transcriptomic and Imaging Data Defines Features of a Favorable Tumor Immune Microenvironment and Identifies a Combination Biomarker for Primary Melanoma

Abstract: ◥Patients with resected stage II-III melanoma have approximately a 35% chance of death from their disease. A deeper understanding of the tumor immune microenvironment (TIME) is required to stratify patients and identify factors leading to therapy resistance. We previously identified that the melanoma immune profile (MIP), an IFN-based gene signature, and the ratio of CD8 þ cytotoxic T lymphocytes (CTL) to CD68 þ macrophages both predict disease-specific survival (DSS). Here, we compared primary with metastatic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
4
14
0
1
Order By: Relevance
“…Top GO terms in the biological process included immune response, inflammatory response, signal transduction, innate immune response and adaptive immune response In addition, all the pathways that were yielded from KEGG analysis were associated with immune response. Consistent with previous studies, our findings verified that immune cells and extracellular matrix play significant roles in building the melanoma microenvironment [19][20][21]. Furthermore, we performed the overall survival analysis of 663 immune-related genes and identified that 600 genes (90.5%) were associated with better outcomes in metastatic melanoma patients.…”
Section: Discussionsupporting
confidence: 90%
“…Top GO terms in the biological process included immune response, inflammatory response, signal transduction, innate immune response and adaptive immune response In addition, all the pathways that were yielded from KEGG analysis were associated with immune response. Consistent with previous studies, our findings verified that immune cells and extracellular matrix play significant roles in building the melanoma microenvironment [19][20][21]. Furthermore, we performed the overall survival analysis of 663 immune-related genes and identified that 600 genes (90.5%) were associated with better outcomes in metastatic melanoma patients.…”
Section: Discussionsupporting
confidence: 90%
“…We first analyze the spatial patterns formed by the infiltrating macrophages in the ABM using 1-PH and the PCF from spatial statistics. Both approaches provide more detailed spatial descriptors than cell counting and have been used to analyze histology data ( 11 , 12 , 34 , 37 ); we have previously validated the use of PCF to describe macrophage infiltration in human tumors by demonstrating that images grouped semiquantitatively by a pathologist share similar statistics ( 34 ). In particular, we quantify the extent to which the macrophages infiltrate the spheroid at each time point in the ABM simulations.…”
Section: Resultsmentioning
confidence: 99%
“…CD68 + TAM in tumor cell nests were described to be associated with a negative prognosis and recurrence in cutaneous melanoma [70]. Furthermore, the ratio of CD8 + T cells to CD68 + macrophages was shown to predict a disease specific survival in melanoma [71]. CD163 + macrophages were reported to accumulate in the TME of melanoma patients resistant to ICI therapy and to play a role in the maintenance of the immunosuppression.…”
Section: Tumor-associated Macrophages (Tam)mentioning
confidence: 99%